2016
DOI: 10.1074/jbc.m116.717744
|View full text |Cite
|
Sign up to set email alerts
|

LRP1 Protein Deficiency Exacerbates Palmitate-induced Steatosis and Toxicity in Hepatocytes

Abstract: LRP1 (LDL receptor-related protein-1) is a ubiquitous receptor with both cell signaling and ligand endocytosis properties. In the liver, LRP1 serves as a chylomicron remnant receptor and also participates in the transport of extracellular cathepsin D to the lysosome for prosaposin activation. The current study showed that in comparison with wild type mice, hepatocytespecific LRP1 knock-out (hLrp1 ؊/؊ ) mice were more susceptible to fasting-induced lipid accumulation in the liver. Primary hepatocytes isolated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 40 publications
3
22
0
Order By: Relevance
“…4). These data suggested that the Mallory-Denk bodies accumulated in livers of HFHC-fed hLrp1 Ϫ/Ϫ mice could not be explained by changes in autophagy activity but were probably the result of lysosomal defects due to LRP1 deficiency, as we have shown previously (11).…”
Section: Hepatic Lrp1 Deficiency Does Not Affect Autophagic Fluxsupporting
confidence: 71%
See 1 more Smart Citation
“…4). These data suggested that the Mallory-Denk bodies accumulated in livers of HFHC-fed hLrp1 Ϫ/Ϫ mice could not be explained by changes in autophagy activity but were probably the result of lysosomal defects due to LRP1 deficiency, as we have shown previously (11).…”
Section: Hepatic Lrp1 Deficiency Does Not Affect Autophagic Fluxsupporting
confidence: 71%
“…Nevertheless, plasma triglyceride, nonesterified fatty acids (NEFA), glucose, and insulin levels are similar to those of hLrp1 ϩ/ϩ mice (10). Deficiency of LRP1 in hepatocytes also promotes lipid accumulation and lipotoxicity in response to excessive fatty acids through lysosomal-mitochondrial permeabilization and endoplasmic reticulum stress (11). Thus, mice with liver-specific LRP1 gene deletion (hLrp1 Ϫ/Ϫ mice) exhibited robust dyslipidemia and hepatosteatosis secondary to hepatic insulin resistance when placed on a high-fat diet (12).…”
mentioning
confidence: 99%
“…LRP1 is also critical for lipid transport and metabolism in adipocytes (12,41,42). It improves the hepatic HDL/ LDL secretion ratio (43) and protects hepatocytes from lipotoxic insults (44). Based on these reports in the literature, LRP1 clearly performs unique functions in a cell type-specific way.…”
Section: Discussionmentioning
confidence: 99%
“…For example, liver-specific knockout of low-density lipoprotein receptor-related protein 1 (LRP1) in mice showed that, following a 24-hour fast, a nearly 7-fold increase in hepatic TAG accumulation was observed as compared to wild-type mice. (66) An accumulation of the autophagic cargo adapter p62 was also noted when isolated LRP -/hepatocytes were incubated in the presence of palmitate, suggesting that global autophagy is impaired when this receptor is perturbed. However, no accumulation of LC3 was observed, suggesting that LRP1 is not involved in the biogenesis of autophagic membranes but rather that lysosome-mediated degradation of LDs had been compromised.…”
Section: Regulation Of Hepatic Lipophagymentioning
confidence: 99%
“…Other factors have recently been shown to participate in the regulation of hepatic lipophagy. For example, liver‐specific knockout of low‐density lipoprotein receptor‐related protein 1 (LRP1) in mice showed that, following a 24‐hour fast, a nearly 7‐fold increase in hepatic TAG accumulation was observed as compared to wild‐type mice . An accumulation of the autophagic cargo adapter p62 was also noted when isolated LRP –/– hepatocytes were incubated in the presence of palmitate, suggesting that global autophagy is impaired when this receptor is perturbed.…”
Section: Regulation Of Hepatic Lipophagymentioning
confidence: 99%